Penggunaan Media Presentasi Berbantuan Aplikasi ISpring Presenter untuk Meningkatkan Penguasaan Konsep dan Keterampilan Berpikir Kritis Mahasiswa pada Materi Asuhan Keperawatan Ibu Postpartum Mata Kuliah Keperawatan Maternitas di STIKes Karsa Husada Garut - Eva Daniati (Jurnal Medika Cendikia, 2017)
Based on the low comprehension of the concept and critical thinking skills of students because students are not much involved in the process of constructing a concept in mind. Therefore, efforts should be made to improve the understand the concept and critical thinking skills with the help of information technology. The aim of this research is to produce interactive learning multimedia that can improve critical thinking skills of students in the subject of nursing maternity at STIKes Karsa Husada Garut. The research used quantitative approach with experiment research method with Non-Equivalent Design Group. The experimental class used presentation media with the Ispring Presenter application, while the control class uses the conventional learning model using the Powerpoint application. Population in this research is 150 students of Study Program of D-III of Nursing level freshman year. There are 60 students divided into 2 classes, 30 students in control class and experiment class 30 students. The result of the research shows that concept and critical thinking of the students before the learning is at a low level, then increases after using Ispring Presenter multimedia. There are significant differences before learning with ISpring Presenter-based presentation media. There is a significant improvement in the critical thinking concepts and skills using Ispring Presenter multimedia. Use of multimedia Ispring Presenter can improve to understand the concept of maternity care materials of postpartum in STIKes Karsa Husada Garut Study Program D-III Nursing. Suggestions submitted, including: in the process of learning, lecturers need to maximize the learning process and learning outcomes. Efforts can be made to maximize the process and learning outcomes can be done by designing and proposing various alternative solutions according to the results of identification of factors that cause failure and support success. Furthermore, the use of appropriate media in the learning process will play a role in increasing the achievement of learning objectives and learning outcomes. With the help of multimedia in learning can help gaining knowledge in every learning activity.